Florida Vegetable Gardening Guide - James M. Stephens; Sydney Park-Brown; Danielle Treadwell; Susan Webb; Amanda Gevens; R. A. Dunn; Gerald Kidder; D. Short; G. W. Simone (EDIS)
Revised! SP-103, a 12-page fact sheet by J.M. Stephens, Sydney Park-Brown, Danielle Treadwell, Susan Webb, Amanda Gevens, R.A. Dunn, G. Kidder, D. Short, and G.W. Simone, provides research-based recommendations appropriate for home gardens. It covers planning, soil preparation, compost and fertilizing, irrigation and drainage, and pest management with and without pesticides. Includes tables with fertilizer and insect control recommendations, a planting guide with planting dates and spacing information, and a table of varieties recommended for Florida gardens. Published by the UF Horticultural Sciences Department, February 2009.